A review on use of social media in teaching and learning - Abdul Mutalib, Masarrah (2015)
Online learning are rapidly evolving in educational uses through social media. Previous research has identified the problem occured where the guidance for appropriate use of social media is needed so that can embark more effective and efficient learning environment. Social media has been shown to have a positive impact towards learner hence making the process of teaching and learning more meaningful. This is because social networking tools can provide opportunities for students to find information, collect their own material, communicate and interact towards each other. Therefore, this concept paper reviews the use of online learning through social media conducted by previous researchers. Besides, the advantages and disadvantages of implementing social media in teaching and learning also beeing reviewed. This review paper describe the use of online learning through social media and also its pros and cons compared to traditional media. As the conclusion, results from the previous research shows that, online learning through social media have a good feedback and advantages that can inline in education purposes.